Carriage of Methicillin-Resistant Staphylococcus Aureus (MRSA) among Health Care Workers of a Tertiary Care Hospital in Non-Outbreak Setting during Routine Infection Control Exercise - Azeem, Rashid (International Journal of Pathology, 2023)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is a type of Staphylococcus that shows resistance to antibiotics like methicillin itself and others such as flucloxacillin, amoxicillin-clavulanate, penicillin, oxacillin and some cephalosporin e.g. cephalexin.Objective: This paper gives an overview of Methicillin-resistant Staphylococcus aureus (MRSA) carriage among health care workers of a tertiary care hospital in order to improve the quality of patient care and to determine the effectiveness of decolonization regime.Materials and Methods: This cross sectional study was conducted in Peshawar institute of Cardiology from February 2022 till August 2022. Our study included 751 staff members both from the clinical and non-clinical areas. After informed consent, nasal sampling was done and MRSA identification was carried out by inoculation on MacConkey agar and blood agar and incubation at 37 ℃ and final reports were obtained within 48 hours. Statistical analyses were performed with Microsoft Excel.Results: MRSA was positive in 116 (15.4%) cases out of 147 (19.5%) Staff members positive for Staphylococcus aureus. In these 116 cases, MRSA positivity was found in 70 (60.9%) clinical staff and in 46(38.8%) non-clinical staff cases. Pearson chi square test showed significant p value of 0.01 in relation to MRSA positivity in clinical staff. Decolonization of MRSA positive cases was done with topical mupirocin which showed 99.1% cases completely decolonized and gave negative cultures.Conclusion: It is suggested MRSA should be recommended in every new patient admission protocol and in every new employee pre-appointment medical examination. Proper hygiene practices and compliance with infection control measures should be strictly followed for the prevention of MRSA dissemination.